Incorporating Inhibition Effects and Hydrolysis Biokinetics into the Mathematical Model of Anaerobic Fermentation - Allen Kurniawan; Yanuar Chandra Wirasembada; Mark L. Sibag; Erizal Erizal; Chusnul Arif (Universitas Diponegoro, 2024)
Anaerobic digestion is a well-known biological treatment process. It uses less energy, consumes fewer nutrients, converts organic pollutants into methane gas, and produces a small quantity of biomass. The interactions among the various microbes in this complex biological system need to be better understood, and as a consequence, mathematical models need to be revised. This review discusses the principles of biokinetic models published in the literature on anaerobic fermentation as part of the anaerobic digestion process for waste-activated sludge. Biokinetic models for anaerobic fermentation have been developed to predict cell growth, substrate consumption, and gas production. This exploration delves into the incorporation of the hydrolysis stage, a multi-step process entailing the breakdown of carbohydrates, proteins, and lipids within existing biokinetic models. Because there is no single analytical method for accurately determining the biokinetics of anaerobic fermentation of waste-activated sludge incorporating hydrolysis parameters and inhibition effects are proposed to improve the estimated trends of process variables as a function of the design variables.